2022
DOI: 10.3389/ijph.2022.1604620
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Interventions to Improve Birth Outcomes: What Are the Effects on Maternal Outcomes? A Scoping Review

Abstract: Objectives: Interventions in pregnancy are commonly evaluated for their effects on birth outcomes because maternal infection and poor nutrition are the primary contributors to adverse pregnancy outcomes, especially in low- and middle-income countries (LMICs). However, the extent to which such interventions directly impact maternal health and nutrition has not been succinctly characterized.Methods: We conducted a scoping review of systematic reviews and meta-analyses of 27 pregnancy interventions to summarize t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Previous study has summarized evidence-based interventions that have been effective in reducing CMM over the past decade, including providing preventive zinc, preventive small-quantity lipid-based nutrient supplements, maternal and child multiple micronutrient powder (MMN), maternal calcium vitamin A supplementation, promotion of breastfeeding, farm input subsidies, appropriate complementary feeding and management of moderate and severe acute malnutrition, etc. ( 7 , 29 , 30 ). These measures have considerably improved the nutritional health of children and pregnant women, thereby decreasing the disease burden caused by CMM ( 31–33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has summarized evidence-based interventions that have been effective in reducing CMM over the past decade, including providing preventive zinc, preventive small-quantity lipid-based nutrient supplements, maternal and child multiple micronutrient powder (MMN), maternal calcium vitamin A supplementation, promotion of breastfeeding, farm input subsidies, appropriate complementary feeding and management of moderate and severe acute malnutrition, etc. ( 7 , 29 , 30 ). These measures have considerably improved the nutritional health of children and pregnant women, thereby decreasing the disease burden caused by CMM ( 31–33 ).…”
Section: Discussionmentioning
confidence: 99%
“…25,26 One in four pregnant women in malaria-endemic African malariaendemic areas was believed to carry a malaria infection at the time of delivery. 27 WHO reported that 34% of pregnancies in the 33 moderate and high-transmission countries of the WHO African Region were exposed to malaria infection in 2020. 2 Because the GBD database lacks data on pregnant women, this article cannot estimate the global burden of malaria among them.…”
Section: Discussionmentioning
confidence: 99%